(untitled) (Scientific journal of the Fergana State University, 2025)
This article is about the role of nitrogen fertilizers in changing the agrochemical properties of light gray soils formed in Southern Fergana, especially in agriculture, the role of nitrogen in the soil and humus, their activity, microbiological processes in the soil, nitrogen accumulators found in the soil. general information about microorganisms and nitrogen fertilizers, which can be used to improve soil fertility, is covered in detail.